Metformin reduces HGF-induced resistance to alectinib via the inhibition of Gab1 - Chen, Hengyi (Cell Death Dis, 2020)
Alectinib is a second-generation anaplastic lymphoma kinase (ALK) inhibitor that has sufficient clinical efficacy and satisfactory safety in ALK-positive non-small cell lung cancer (NSCLC) patients with or without brain metastasis. Alectinib has now become an important drug in the first-line treatment of advanced ALK-positive NSCLC; however, resistance is almost inevitable. The increased expression of hepatocyte growth factor (HGF) and its physiological receptor tyrosine kinase MET have been shown to be linked to acquired resistance to various tyrosine kinase inhibitors (TKIs), and this phenomenon has been observed in some ALK-positive NSCLC tumour tissues. In this study, we found that HGF levels in the culture supernatant of an ALK-positive cell line tended to increase with time and could be further increased by alectinib in a time-dependent manner. Exogenous or endogenous HGF did not cause resistance to the ALK/MET double-targeted small molecule inhibitor crizotinib, but it was an important cause of alectinib resistance. Furthermore, Gab1 was a key effector in the HGF/MET signal transduction pathway that mediated alectinib resistance. The antidiabetic drug metformin combined with alectinib overcame alectinib resistance triggered by HGF/MET through disrupting the complex between MET and Gab1, thereby inhibiting Gab1 phosphorylation and the activation of downstream signal transduction pathways. These results suggest that metformin combined with alectinib may be useful for overcoming alectinib resistance induced by the activation of the HGF/MET signalling pathway and improving the efficacy of alectinib.